From Divergence to Convergence: Towards Integration of Cognitive Linguistics and Critical Discourse Analysis in Political Discourse - WANG, QIAN (Advances in Social Sciences Research Journal, 2019)
The social turn of cognitive linguistics and cognitive turn of critical discourse analysis breed the opportunity for cognitive linguistics and critical discourse analysis to develop towards a more converging path that integrates both cognitive and social dimensions of language. As known, political discourse is intrinsically persuasive and always informs a power relation with attempts to achieve effectiveness of persuasion. This paper argues that both approaches (Cognitive Linguistics and CDA) are concerned with surfaced evidence of implicit ideologies hidden behind political discourse, so the integration of CL and CDA could extend the research scope for both paradigms on one hand, and provide more powerful explanatory tools to augment our understanding of the intertwined relations between language, cognition and society on the other.